2019
DOI: 10.4022/jafib.2154
|View full text |Cite
|
Sign up to set email alerts
|

Role of Prophylactic Magnesium Supplementation in Prevention of Postoperative Atrial Fibrillation in Patients Undergoing Coronary Artery Bypass Grafting: a Systematic Review and Meta-Analysis of 20 Randomized Controlled Trials.

Abstract: Background : Several randomized trials have evaluated the efficacy of prophylactic magnesium (Mg) supplementation in prevention of post-operative atrial fibrillation (POAF) in patients undergoing cardiac artery bypass grafting (CABG). We aimed to determine the role of prophylactic Mg in 3 different settings (intraoperative, postoperative, intraoperative plus postoperative) in prevention of POAF. Methods: A systemic literature search was performed (until January 19, 2019) using PubMed, EMBASE, Web of Science, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…On the contrary, in a study by Solomon et al in patients undergoing CABG, magnesium in combination with propranolol was not shown to further reduce the incidence of POAF compared to propranolol alone but significantly increased the incidence of hypotensive episodes [73]. Two meta-analyses confirmed the efficacy of magnesium in reducing POAF incidence after cardiac surgery [74,75]. Regarding the prevention of POAF with magnesium after non-cardiac thoracic surgery, as far as we know, the only available study, which showed the efficacy of this electrolyte, was carried out by Terzi et al in 1996 [76].…”
Section: Magnesiummentioning
confidence: 95%
“…On the contrary, in a study by Solomon et al in patients undergoing CABG, magnesium in combination with propranolol was not shown to further reduce the incidence of POAF compared to propranolol alone but significantly increased the incidence of hypotensive episodes [73]. Two meta-analyses confirmed the efficacy of magnesium in reducing POAF incidence after cardiac surgery [74,75]. Regarding the prevention of POAF with magnesium after non-cardiac thoracic surgery, as far as we know, the only available study, which showed the efficacy of this electrolyte, was carried out by Terzi et al in 1996 [76].…”
Section: Magnesiummentioning
confidence: 95%
“…These channels are typically activated by low concentrations of free magnesium [ 22 ]. In the Framingham Heart Study, it was shown low magnesium level after cardiac surgery was an indication for the onset of POAF [ 23 , 24 ]. A meta-analysis showed that treating patients prophylactically with magnesium in the post-operative period only led to a statistically significant decrease in POAF [ 25 ], suggesting the use of intravenous magnesium as an alternative to prevent POAF.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed mechanism for hypomagnesium contributing to POAF is due to dilution from transfusion during surgery [ 47 ]. There has been debate in the literature about magnesium supplementation for treatment of POAF, and a meta-analysis showed that post-operative magnesium supplementation was the only time frame that significantly reduced the risk of POAF [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The greatest attention has been pointed to the prevention of arrhythmias in high-risk patients undergoing cardiac surgery. A recent meta-analysis is supporting the data published in previous years on the role of prophylactic magnesium supplementation in the prevention of postoperative atrial fibrillation (POAF) in patients undergoing cardiac surgery [ 33 ], especially when magnesium is given in the postoperative period [ 34 ]. Perioperative hypomagnesemia should have a crucial influence on cardiac adverse events after surgery [ 35 ] particularly on POAF, described as the most common cardiac complication occurred in cardiothoracic surgery [ 36 ].…”
Section: Ionized Vs Total Magnesium Levels In the Perioperative Settingmentioning
confidence: 72%